2017
DOI: 10.1002/polb.24385
|View full text |Cite
|
Sign up to set email alerts
|

Competition between supernucleation and plasticization in the crystallization and rheological behavior of PCL/CNT-based nanocomposites and nanohybrids

Abstract: PCL was blended with pristine multiwalled carbon nanotubes (MWCNT) and with a nanohybrid obtained from the same MWCNT but grafted with low molecular weight PCL, employing concentrations of 0.25 to 5 wt % of MWCNT and MWCNT-g-PCL. Excellent CNT dispersion was found in all samples leading to supernucleation of both nanofiller types. Nanohybrids with 1 wt % or less MWCNTs crystallize faster than nanocomposites (due to supernucleation), while the trend eventually reverses at higher nanotubes content (because of pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 101 publications
4
21
0
Order By: Relevance
“…This result indicated that the CNTs supernucleation could be dominated by (i) the strong interaction between the polymer and the MWCNTs and (ii) the dispersion quality of the blend. A similar or better supernucleation effect was reported when PCL was blended with PCL grafted MWCNTs (MWCNTs-g-PCL) [69]. The supernucleation effect of the MWCNTs was the result of an excellent dispersion of the MWCNTs in the polymer matrix.…”
Section: Nucleation and Crystallization Behavioursupporting
confidence: 64%
See 4 more Smart Citations
“…This result indicated that the CNTs supernucleation could be dominated by (i) the strong interaction between the polymer and the MWCNTs and (ii) the dispersion quality of the blend. A similar or better supernucleation effect was reported when PCL was blended with PCL grafted MWCNTs (MWCNTs-g-PCL) [69]. The supernucleation effect of the MWCNTs was the result of an excellent dispersion of the MWCNTs in the polymer matrix.…”
Section: Nucleation and Crystallization Behavioursupporting
confidence: 64%
“…Generally, neat PCL revealed Avrami index values of approximately n = 3. This indicates that (i) the crystal geometry is spherulitic and follows an athermal nucleation which leads to spherulites of roughly the same size during isothermal crystallization, and that (ii) the nucleation is very fast (instantaneous), and the nucleation starts almost immediately after the isothermal crystallization temperature was reached [47,66,69]. Trujillo et al [66] reported lower Avrami index values (approximately n = 2) for PCL/CNT nanocomposite systems compared to the n = 3 for neat PCL, corresponding to the formation of axialites.…”
Section: Nucleation and Crystallization Behaviourmentioning
confidence: 98%
See 3 more Smart Citations